Impact of climate change on long-term variations of small yellow croaker (Larimichthys polyactis) winter fishing grounds - Zhang, Rui; Liu, Yang; Tian, Hao; Liu, Shuhao; Zu, Kaiwei; Xia, Xinmei (Frontiers in Marine Science, 2022)
Small yellow croaker (Larimichthys polyactis) is one of the key demersal species with high economic values and wide distribution in the China Seas. In this study, a winter fishing grounds abundance index (WFAI) was developed by using fisheries survey data in 1971-1982 and used as the response variable to investigate the impacts of environmental variables, including surface current velocity (SCV), sea surface salinity (SSS), sea surface temperature (SST) and depth (DE). A total of 45 combinatorial generalized additive models (GAMs), generalized linear models (GLMs) and random forest models (RFs) were used to select the optimal WFAI prediction. The final WFAI distribution results showed that the winter fishing ground hotspots of small yellow croaker were mainly distributed between 11℃, 16℃ isotherms and 50m, 100m isobaths, and the area of winter fishing ground hotspots (WFHA) significantly decreased and the hotspots tended to move northward over the past 50 years. The shape of hotspots was strongly affected by temperature fronts and salinity fronts. Analysis with the climate indices revealed that Atlantic Multidecadal Oscillation (AMO) might have a large influence on the distribution of small yellow croaker by affecting SST and SSS in the China Seas more than Pacific Decadal Oscillation (PDO), North Pacific Gyre Oscillation (NPGO), Arctic Oscillation Index (AOI). The future prediction based on two extreme scenarios (RCP2.6, and RCP8.5) indicated that the hotspots would obviously move northward. These findings will serve effectively the resources monitoring, management, and evaluation of small yellow croaker in the China Seas.